Association Between Serum Calcium and the Prevalence of Hypertension Among US Adults - Hua, Yang; Liu, Heng-li; Sun, Jin-Yu; Kong, Xiang-Qing; Sun, Wei; Xiong, Ya-Qing (Frontiers in Cardiovascular Medicine, 2021)
Background Hypertension is a significant risk factor of cardiovascular diseases, posing a serious threat to global health. Calcium plays an important role in regulating body homeostasis. The association of calcium with hypertension remains uncertain in the general population. Methods and results Cross-sectional data from the 2007-2018 National Health and Nutrition Examination Survey were analyzed. Adjusted multivariable logistic regression analysis and restricted cubic spline were used to investigate the association of serum calcium with the prevalence of hypertension. A total of 26,778 participants were included. The increase in calcium levels showed a positive association with the prevalence of hypertension in all three models with ORs of 1.347 (1.249-1.454), 1.522(1.401~1.654), and 1.438 (1.306~1.583). The further subgroup analysis demonstrated a robust trend across all categories. The restricted cubic spline plot exhibited an S-curve relationship between calcium and hypertension. Conclusion Our studies demonstrated a significant association between higher serum calcium levels and the prevalence of hypertension. Our findings highlighted serum calcium levels in hypertensive patients.